2003
DOI: 10.1002/j.2164-490x.2003.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Training in Group Counseling: Humanistic Processes in Practice

Abstract: D. A. Kolb's (1984) 4 processes of experiential education are presented as guidelines for humanistically based training in group counseling. Specific training activities are described, and recommendations for improving training methods are outlined. The authors present qualitative data obtained from graduate counseling students who participated in these activities and provide recommendations for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…3). Counselor education has a history of valuing EL in training (Arthur & Achenbach, 2002;Falco & Bauman, 2004;Goodrich & Luke, 2010;Luke & Kiweewa, 2010;Osborn, Daninhirsch, & Page, 2003) as it deepens the level of understanding and personal growth of CITs (Arthur & Achenbach, 2002;Ferch, St. John, & Ramsey, 2006;Harrawood, McClure, & Nelson, 2011;Kiweewa, Gilbride, Luke & Seward, 2013;Luke & Kiweewa, 2010). Critical to counselor development, EL fosters self and other awareness by accessing cognitive and affective stages of learning (Arthur & Achenbach, 2002;Falco & Bauman, 2004;Goodrich & Luke, 2010;Harel, et al, 2012;Luke & Kiweewa, 2010).…”
Section: Experiential Learning In Counselor Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Counselor education has a history of valuing EL in training (Arthur & Achenbach, 2002;Falco & Bauman, 2004;Goodrich & Luke, 2010;Luke & Kiweewa, 2010;Osborn, Daninhirsch, & Page, 2003) as it deepens the level of understanding and personal growth of CITs (Arthur & Achenbach, 2002;Ferch, St. John, & Ramsey, 2006;Harrawood, McClure, & Nelson, 2011;Kiweewa, Gilbride, Luke & Seward, 2013;Luke & Kiweewa, 2010). Critical to counselor development, EL fosters self and other awareness by accessing cognitive and affective stages of learning (Arthur & Achenbach, 2002;Falco & Bauman, 2004;Goodrich & Luke, 2010;Harel, et al, 2012;Luke & Kiweewa, 2010).…”
Section: Experiential Learning In Counselor Educationmentioning
confidence: 99%
“…Additionally, homework assignments such as identifying an object or event within daily life (such as the sound of a telephone) to serve as a mindfulness reminder, are incorporated to increase individual focus on awareness of internal thoughts and feelings and external stimuli (Hanh, 1975, Stauffer & Pehrsson, 2012. Facilitated group processing, reflective journal writing, and facilitator feedback are integrated into the experience to promote personal growth and development (Osborn et al, 2003). Each week members are asked to reflect in writing on their group experience articulating what was learned about self, self in relation to the group, and about the group members.…”
Section: Phase Iii: Mindful Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Luke and Kiweewa (2010) observed that the absence of empirical data has not only limited our ability to understand what beneficial factors may be associated with experiential group participation, but also has hindered the development of effective training models to facilitate counseling students' personal growth and awareness during experiential group training. Some authors have explained this lack of research as a reflection of theoretical and methodological inconsistencies in general (Arthur & Achenbach, 2002;Osborn, Daninhirsch, & Page, 2003), whereas others have suggested that efforts to identify helpful factors related to experiential group participation have been hampered by the limited efforts to distinguish between experiential groups and therapy groups (e.g., Merta et al, 1993). According to Merta et al (2003), the simultaneous focus on personal issues and the learning of group process and skills differentiates experiential groups from therapy groups, which are primarily focused on personal change.…”
Section: Experiential Groups In Counselor Educationmentioning
confidence: 99%
“…These include applications to counselor education and supervision (Abbey et al 1985;Murrell and Claxton 1987;Osborn et al 2003), judicial education (Claxton and Murrell 1992), criminal justice education (Claxton 1997), and marketing education (Frontczak 1998). Svinick and Dixon's (1987) work, cited above, included examples from several disciplines, among them pharmacy, public policy, history, architecture, engineering, and psychology.…”
Section: Kolb's Theory and Implications For Teaching And Curriculum Imentioning
confidence: 99%